Quantifying anterior knee pain during specific activities after using the bone-patellar tendon-bone graft for arthroscopic anterior cruciate ligament reconstruction - Khorpong Kovindha; Phob Ganokroj; Pisit Lertwanich; Bavornrat Vanadurongwan (Elsevier, 2019)
Background/objective: There has been much debate about the optimal graft choice for an anterior cruciate ligament (ACL) reconstruction. Anterior knee pain is a common donor site problem when using a bone-patellar tendon-bone (BPTB) graft. However, knowledge of the characteristics of anterior knee pain during different daily activities is still limited. This study aimed to determine the incidence of anterior knee pain and to quantify the degree of pain during a range of daily living activities. Methods: Thirty-five patients who were scheduled to undergo an ACL reconstruction with an autologous BPTB graft between February 2015 and December 2016 were enrolled. A visual analogue scale (VAS) for pain was recorded during each of the following activities: ascending at 30-degree slope, ascending and descending stairs, running, jumping, squatting, kneeling, sitting cross-legged, and sitting one-legged. Demographic data, the range of motion, the area of decreased sensation, and the IKDC score were collected and compared 3 and 6 months postoperatively. Results: The 35 male patients had a mean age of 29.7 years. Postoperatively, the mean IKDC scores were 58.1 ± 9.8 at 3 months and 72.7 ± 10.5 at 6 months. The incidences of overall anterior knee pain were 62.9% and 34.3% at the 3- and 6-month time points. Kneeling was the only activity that produced severe pain. At 3 months postoperatively, kneeling's mean VAS pain score was 3.9 ± 2.9 (2.9, 4.9; 95% CI for mean for 17 patients [48.5%] with considerable pain), whereas at 6 months postoperatively, it was 2 ± 2.5 (1.2-2.9; 95% CI for mean for 9 patients [25.7%] with considerable pain). The area of numbness of the proximal leg decreased from 12.8 ± 18.3 cm2 (6.4, 19.2; 95% CI for mean) to 3.2 ± 9.1 cm2 (0.1, 6.5; 95% CI for mean) at 3 and 6 months postoperatively. Conclusions: Kneeling was the most challenging activity in terms of creating considerable levels of anterior knee pain in patients who had undergone an ACL reconstruction using a BPTB graft. Other knee activities, however, did not create moderate or severe degrees of anterior knee pain. Both anterior knee pain and numbness at the proximal leg improved over time.Trial registration number: TCTR2018-0630002. Keywords: Anterior cruciate ligament reconstruction, Anterior knee pain, Bone-patellar tendon-bone graft, Incidence and kneeling